2005
DOI: 10.4049/jimmunol.174.10.6195
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Dimethyl Sulfoxide Augmentation of IL-1β Production

Abstract: Expression of the inflammatory cytokine IL-1β occurs in various inflammatory diseases, and IL-1β production is regulated at multiple levels. There are conflicting reports about the effects of antioxidants on IL-1β production. In this study, we investigated the regulatory role of the antioxidant DMSO on LPS-stimulated IL-1β gene expression in human PBMC and in vivo. This study demonstrated that 1% DMSO increased LPS-stimulated (50 ng/ml) IL-1β secretion in a dose- and time-dependent manner without altering TNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 54 publications
6
21
1
Order By: Relevance
“…We acknowledge that a DMSO vehicle control was not included in two experiments shown in Figs 5 and 6. High concentrations of DMSO (1–2% [vol/vol]) have been shown to augment the LPS effect on immune cells (i.e., increase inflammatory cytokine secretion) [90]; therefore, in our study, the relative effect of TAK-242 on the LPS response may have been weakened. Nevertheless, previous studies have shown that, even at concentrations as high as 1–2% (vol/vol), DMSO has no effect on NF-κB activity in various cell lines, reducing this concern [9092].…”
Section: Discussionmentioning
confidence: 90%
“…We acknowledge that a DMSO vehicle control was not included in two experiments shown in Figs 5 and 6. High concentrations of DMSO (1–2% [vol/vol]) have been shown to augment the LPS effect on immune cells (i.e., increase inflammatory cytokine secretion) [90]; therefore, in our study, the relative effect of TAK-242 on the LPS response may have been weakened. Nevertheless, previous studies have shown that, even at concentrations as high as 1–2% (vol/vol), DMSO has no effect on NF-κB activity in various cell lines, reducing this concern [9092].…”
Section: Discussionmentioning
confidence: 90%
“…DMSO possesses anti-inflammatory properties (Melchior et al, 2003), as well as the ability to act as a free radical scavenger (Xing and Remick, 2005). Thus, its properties have been exploited in the treatment of dermatological, rheumatic and renal manifestations of amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
“…DMSO possesses anti-inflammatory properties [4], as well as the ability to act as a free radical scavenger [5]. Thus, its properties have been exploited in the treatment of dermatological, rheumatic, and renal manifestations of amyloidosis.…”
Section: Introductionmentioning
confidence: 99%